1994
DOI: 10.1289/ehp.94102125
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of the developing brain to thyroid abnormalities: environmental insults to the thyroid system.

Abstract: Neurologic development follows orderly patterns that can be severely disturbed when thyroid hormones are deficient or excessive. Should this occur at appropriate development periods, irreversible neurologic damage can result. The nature of the deficits depends upon the specific development period and the severity of the thyroid disturbance. PCBs and dioxins are structurally similar to the thyroid hormones. Their binding characteristics are similar to those of thyroid hormones and all three groups bind to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(64 citation statements)
references
References 59 publications
(69 reference statements)
0
64
0
Order By: Relevance
“…Irreversible neurologic damage resembling that seen in those exposed to thyroid hormone deficiency in utero and/or in infancy was also observed (2,11). In occupationally exposed workers, an increased prevalence of thyroid disorders and thyroid cancer (12,13) has been reported.…”
Section: Introductionmentioning
confidence: 85%
“…Irreversible neurologic damage resembling that seen in those exposed to thyroid hormone deficiency in utero and/or in infancy was also observed (2,11). In occupationally exposed workers, an increased prevalence of thyroid disorders and thyroid cancer (12,13) has been reported.…”
Section: Introductionmentioning
confidence: 85%
“…45 TH plays a crucial role during brain development, and disturbances in TH homeostasis can cause serious impairment in neurological development. 46,47 Therefore, it has been proposed that a disruption of TH homeostasis may explain the neurotoxicity of PBDEs. 12 Our previous study demonstrated that 150 days of exposing zebrafish embryos to DE-71 (1, 3, 10 μg/L) can elevate TH levels in adults and that increased TH levels are also transferred to F1 eggs.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…The latter hypothesis is based on the fact that brain development is highly dependent on thyroid hormones (114). PCBs and PCDDs that, like PBDEs, alter the thyroid hormone homeostasis have been suggested to disrupt brain development, resulting in permanent neurologic damage (115,116).…”
Section: Experimental Studies In Animalsmentioning
confidence: 99%
“…Because the development of the central nervous system is highly dependent on thyroid hormones, alterations in thyroid homeostasis may result in permanent neurobehavioral defects (114,115). It may also be the primary cause of neurodevelopmental toxicity of PBDEs.…”
Section: Experimental Studies In Animalsmentioning
confidence: 99%